Correlation of Sikora and Smith-McLean- Pratt Soil Buffer pH Measurements - B. Rutter; D. A. Ruiz Diaz; J. Thomas (Kansas Agricultural Experiment Station Research Reports, 2019)
Historically, the K-State Research and Extension Soil Testing Laboratory has used the Smith-McLean-Pratt (SMP) buffer solution to estimate total soil acidity and estimate lime recommendations. The SMP solution contains hazardous chemicals and poses a health risk to lab workers. The Sikora buffer solution was designed as a replacement for SMP and contains no hazardous chemicals. A study was conducted to investigate the relationship between these two buffers in Kansas soils. A strong positive correlation was observed between SMP and Sikora buffer pH measurements. However, linear regression suggests that the relationship is not 1:1 (slope = 0.88). Therefore recommendation equations using the Sikora buffer would require different equations than those currently used for the SMP buffer pH measurements.
Keywords: pH; Sikora; SMP; buffer pH